Is Foreign Debt Portfolio Management Efficient in Emerging Economies? - Hussein, Khaled (IMF Working Papers; Working Paper ;, 2001)
This paper develops a simple model of foreign debt portfolio management. The model suggests that, under mild conditions, the currency composition of a country's foreign debt portfolio is responsive to exchange rate movements. Empirical evidence is provided for a panel of 14 emerging economies in the period 1970-98. Attention is focused on the stocks of foreign liabilities denominated in U.S. dollars, deutsche marks (DM), Japanese yen, and Swiss francs. The results of the empirical analysis show that foreign debt portfolio management has been sub-optimal in the countries under examination. In these countries, the currency composition of foreign debt has not reflected a substitution effect away from the currencies that have appreciated over time vis-a-vis the U.S. dollar.